Improvement of the energy processes analysis method of electromechanical systems with semiconductor converters - Atef Saleh, Al-Mashakbeh (Eastern-European Journal of Enterprise Technologies, 2017)
The paper presents the improvement of the method for the analysis of energy processes in electric circuits with semiconductor converters by means of a commutation function. The improvement has been achieved due to the realization of the frequency domain with the use of the discrete convolution algorithm. The proposed method has been verified taking an electric circuit with a sinusoidal-power controlled key voltage regulator with active-inductive load as an example. The correction of the analytical expressions of the commutation function, voltage, current and power, determined in the frequency domain, has been verified by comparison of the curves plotted on the basis of the obtained analytical expressions and the curves plotted by means of the inverse Fourier transform of the results of electric signals operations in the frequency domain. It has been demonstrated that this method makes it possible to simplify the analytical calculation and achieve its automation and obtain the predicted result.